Treatment satisfaction of patients with psoriasis with topical therapy in a real-world setting: unmet need for higher effectiveness - Ninosu, Nadia Nicole; Hölker, Suna; Kappenstein, Max; Büttner, Sylvia; Peitsch, Wiebke K.; Schaarschmidt, Marthe-Lisa (The journal of dermatological treatment, 2023)
Background Topical medication is the mainstay for treatment of mild psoriasis. However, dissatisfaction with topicals is common and rates of non-adherence are high. Assessing patients’ perspectives can help to identify unmet needs.Objective Our aim was to investigate satisfaction of patients with psoriasis with topical therapy and to determine influencing factors.Methods Patients were recruited from the Department of Dermatology, University Medical Center Mannheim, Germany. Satisfaction was assessed using the Treatment Satisfaction Questionnaire for Medication version 1.4 with the domains effectiveness, side effects, convenience, and global satisfaction (scale 0-100 each). The impact of sociodemographic and disease characteristics was determined by multivariate regression.Results Averaged across the cohort (n = 122, mean age 52.5 years, 58.2% male), the side effects domain had the highest mean satisfaction score (89.7), followed by convenience (72.5), global satisfaction (60.8), and effectiveness (55.0). Comparing specific medications, combinations of corticosteroids and vitamin D analogues were rated best in effectiveness. Treatment satisfaction was influenced by age, partnership, ability to apply topicals independently, disease-related quality-of-life impairment, sole or adjunctive use of topicals and pruritus.Conclusions Participants were particularly satisfied with safety but rather dissatisfied with effectiveness of topicals. Topical therapy should be adapted to individual needs with special attention to effectiveness.